Patient and surgeon perspectives of a large-scale system for automated, real-time monitoring and feedback of shared decision-making integrated into surgical practice: a qualitative study - Leila Rooshenas; Jane M Blazeby; Andrew Smith; Angus G K McNair; Andrew Judge; Michael R Whitehouse; Christie Cabral; Jessica Preshaw; Barnaby Reeves; Shelley Potter; Kerry N L Avery; Philip Braude; et al. (BMJ Open)
Objective To explore patient and healthcare professional perceptions about the acceptability and impact of a large-scale system for automated, real-time monitoring and feedback of shared decision-making (SDM) that has been integrated into surgical care pathways.Design Qualitative, semistructured interviews were conducted with patients and healthcare professionals between June and November 2021. Data were analysed using deductive and inductive approaches.Setting Large-scale monitoring of SDM has been integrated in NHS surgical care across two large UK National Health Service Trusts.Participants Adult surgical patients (N=18, 56% female), following use of an SDM real-time monitoring and feedback system, and healthcare professionals (N=14, 36% female) involved in their surgical care. Patient recruitment was conducted through hospital research nurses and professionals by direct approach from the study team to sample individuals purposively from seven surgical specialties (general, vascular, urology, orthopaedics, breast, gynaecology and urgent cardiac).Results 10 themes were identified within three areas of exploration that described factors underpinning: (1) the acceptability of large-scale automated, real-time monitoring of SDM experiences, (2) the acceptability of real-time feedback and addressing SDM deficiencies and (3) the impact of real-time monitoring and feedback. There was general support for real-time monitoring and feedback because of its perceived ability to efficiently address deficiencies in surgical patients’ SDM experience at scale, and its perceived benefits to patients, surgeons and the wider organisation. Factors potentially influencing acceptability of large-scale automated, real-time monitoring and feedback were identified for both stakeholder groups, for example, influence of survey timing on patient-reported SDM scores, disease-specific risks, patients’ dissatisfaction with hospital processes. Factors particularly important for patients included concerns over digital exclusion exacerbated by electronic real-time monitoring. Factors unique to professionals included the need for detailed, qualitative feedback of SDM to contextualise patient-reported SDM scores.Conclusions This study explored factors influencing the acceptability of automated, real-time monitoring and feedback of patients’ experiences of SDM integrated into surgical practice, at scale among key stakeholders. Findings will be used to guide refinement and implementation of SDM monitoring and feedback prior to formal development, evaluation and implementation of an SDM intervention in the NHS.Trial registration number ISRCTN17951423.The original protocol doi: 10.1136/bmjopen-2023-079155.